Increased expression of astrocyte markers in schizophrenia: Association with neuroinflammation. (August 2014) - Catts, Vibeke Sørensen; Wong, Jenny; Fillman, Stu Gregory; Fung, Samantha Jane; Shannon Weickert, Cynthia
Objective: While schizophrenia may have a progressive component, the evidence for neurodegenerative processes as indicated by reactive astrocytes is inconclusive. We recently identified a subgroup of individuals with schizophrenia with increased expression of inflammatory markers in prefrontal cortex, and hypothesized that this subgroup would also have reactive astrocytes. Method: We measured glial fibrillary acidic protein (GFAP) mRNA by quantitative real-time reverse transcriptase polymerase chain reaction (RT-PCR) and protein levels by immunoblotting in grey matter homogenate from 37 individuals with schizophrenia and 37 unaffected controls. We examined the morphology of GFAP-positive astrocytes in immunostained sections of middle frontal gyrus. We tested if GFAP expression or astrocyte morphology were altered in people with schizophrenia with increased expression of inflammatory markers. We used RNA-Seq data on a subset of patients and controls ( n =20/group) to ascertain whether mRNA transcripts associated with astrogliosis were elevated in the individuals with active neuroinflammation. Results: GFAP (mRNA and protein) levels and astrocyte morphology were not significantly different between people with schizophrenia and controls overall. However, individuals with schizophrenia with neuroinflammation had increased expression of GFAP mRNA ( t (33)=2.978, p =0.005), hypertrophic astrocyte morphology (χ 2 (2)=6.281, p =0.043), and statistically significant elevated expression of three mRNA transcripts previously associated with astrogliosis. Conclusions: We found clear evidence of astrogliosis in a subset of people with schizophrenia. We suggest that the lack of astrogliosis reported in previous studies may be due to cohort differences in aetiopathology, illness stage, treatment exposure, or a failure to examine subsets of people with schizophrenia.